PENGARUH PENGGUNAAN HYDROCARBON CRACK SYSTEM (HCS) DAN JENIS BUSI TERHADAP KANDUNGAN EMISI GAS BUANG MESIN K3 VE - Rizyan, Nandhika; Wahyudi (Universitas Negeri Semarang, 2025)
Technology is developing more rapidly as time goes by. This development has an impact on high community mobility activities, so that the need for motorized vehicles also increases. The more motorized vehicles there are, the more exhaust gas emissions will pollute the environment. This research aims to determine the effect of using a Hydrocarbon Crack System (HCS) catalyst and the type of spark plug in motor vehicle engines on exhaust emissions. The research method used was an experimental approach regarding the use of the HCS catalyst and the type of spark plug used in the K3 VE engine. This research uses a maximum of 2 HCS catalyst number testing variations with standard and platinum spark plug types. Emission testing using the Qrotech QRO-401 Gas Analyzer to measure the results of exhaust emissions from motorized vehicles. The test results obtained data on CO and HC gas levels from exhaust emissions. The research results show that the use of HCS and this type of spark plug can reduce motor vehicle exhaust emissions. The best reduction in exhaust emissions is when using 2 HCS catalysts. The use of 2 HCS catalysts and standard spark plugs at 750 rpm CO gas decreased by 33.3% and HC gas decreased by 18% from before using HCS. The reduction in exhaust emissions also occurred when using this type of spark plug, using platinum spark plugs at 750 rpm CO gas decreased by 26.7% and HC gas decreased by 8.7% compared to using standard spark plugs. The best reduction in exhaust emissions occurred when using 2 HCS catalysts and platinum spark plugs, at 750 rpm CO gas fell to 0.07% from the previous 0.15% under standard conditions. HC gas also fell to 123 ppm from the previous 160 ppm under standard conditions. Combining the use of an HCS catalyst and this type of spark plug can reduce exhaust emissions maximally. The use of an HCS catalyst and this type of spark plug has been proven to be able to reduce motor vehicle exhaust emissions and produce more environmentally friendly exhaust emissions in accordance with the Decree of the Minister of the Environment Number 8 of 2023, concerning thresholds for motor vehicle exhaust emissions.